Dual Gold Catalysis: Synthesis of Polycyclic Compounds via CH Insertion of Gold Vinylidenes. Issue 49 (8th October 2014) - Wieteck, Marcel; Tokimizu, Yusuke; Rudolph, Matthias; Rominger, Frank; Ohno, Hiroaki; Fujii, Nobutaka; Hashmi, A. Stephen K.
Abstract New and interesting polycyclic compounds have been synthesized from non‐conjugated diyne systems by dual gold catalysis. A quaternary carbon center in the backbone and the accompanying Thorpe–Ingold effect enabled the unprecedented insertion of sp3 and sp2 CH bonds that for the first time were incorporated within the backbone of the diyne system and allowed the construction of complex polycyclic carbon scaffolds inaccessible by previous approaches in which the CH bonds for the insertion were situated at the other end of the alkyne.